2014
DOI: 10.1007/s11356-014-3574-4
|View full text |Cite
|
Sign up to set email alerts
|

Chloroethene degradation and expression of Dehalococcoides dehalogenase genes in cultures originating from Yangtze sediments

Abstract: The anaerobic Dehalococcoides spp. is the only microorganism known to completely dechlorinate the hazardous compounds tetrachloroethene (PCE) or trichloroethene (TCE) via dichloroethene (DCE) and vinyl chloride (VC) to the terminal product, ethene. In this study, growth of Dehalococcoides spp. (DHC) and the expression of DHC dehalogenase genes were demonstrated for Yangtze enrichment cultures. Reductive dechlorination of chloroethenes occurred in Yangtze sediment without the addition of any external auxiliary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Many studies demonstrated that Dehalococcoides spp. is a bacterial genus known to completely dechlorinate the hazardous compounds PCE and TCE via DCE and VC to the terminal product, ethane ( Aktaş et al, 2012 ; Löffler et al, 2013 ; Kranzioch et al, 2015 ). Recently, Cichocka et al (2010) investigated on reductive dechlorination (RD) of tetrachloroethene to ethene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies demonstrated that Dehalococcoides spp. is a bacterial genus known to completely dechlorinate the hazardous compounds PCE and TCE via DCE and VC to the terminal product, ethane ( Aktaş et al, 2012 ; Löffler et al, 2013 ; Kranzioch et al, 2015 ). Recently, Cichocka et al (2010) investigated on reductive dechlorination (RD) of tetrachloroethene to ethene.…”
Section: Introductionmentioning
confidence: 99%
“…During dechlorination, an increase in gene copy numbers of pceA, tceA , and vcrA , was observed ( Poritz et al, 2013 ; Kranzioch et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradation of organic pollutants and nitrogen-containing compounds (nitrate, nitrite, ammonia) as beneficial ecosystem services is investigated by using modern PCR-techniques [19, 20] as well as by isotope fractionation [2628] within laboratory degradation studies with original Taihu materials. Powerful PCR methods are also used to detect microorganisms having harmful effects such as bacteria with antibiotic resistance genes [29] as well as pathogenic viruses and bacteria, originating e.g.…”
Section: Research Topics—around the Whole Water Cyclementioning
confidence: 99%
“…DDT is a typical organic compound characterized by high bioaccumulability, toxicity, and persistence aquatic environments and is, therefore, important to many lakes. The microbiological transformation of chlorinated pollutants in Yangtze River sediments has been demonstrated recently (Kranzioch et al 2013(Kranzioch et al , 2015. Huang et al (2014a) modeled the effects of environmental variables on short-term spatial changes in phytoplankton biomass in the Lake Taihu.…”
Section: Lakes In China-taihumentioning
confidence: 99%